Designing the data information system of Lecturers’ research in Kopertis Wilayah II Palembang - Sutedi Sutedi (Politeknik Negeri Lampung, 2014)
It is important for lecturers to improve the quantity and quality of their research. To support this, Kopertis Wilayah II oftenly provides some grants for the lecturers to improve their research. With more research carried out, good data information system of lecturers’ research is needed. Making use of information technology can be a solution to fulfill the need of information related to the lecturers’ research as well as to check the lecturers’ research data to minimize the plagiarism practices and the problems of redundancies in lecturers title of research.Keywords : information system, Information technology, plagiarism, redundancies